The Influence of Social Media Marketing, Hedonic Shopping Motivation and Electronic Word of Mouth Towards Impulse Purchases for Shopee’s Customers in Medan - Candice Yap Yap; Genesis Sembiring Depari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper aims to research regarding the impacts that social media marketing, hedonic shopping motivation and electronic word of mouth has to a Shopee customer’s impulse purchases. The method applied in this study is quantitative and data will be collected by providing online to Shopee’s customers located in Medan, Indonesia. Convenience sampling method will be used and the sample will be distributed to whom the writer can easily distribute to. From the questionnaires distributed, 97 respondent’s data were obtained and they will be processed with the SPSS statistical software program. Result shows that only hedonic shopping motivation will significantly impact the impulse purchases made by Shopee customers in Medan while the others will not much impact to impulse purchases.